2009
DOI: 10.1007/s11936-009-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Unusual causes of intermittent claudication: Popliteal artery entrapment syndrome, cystic adventitial disease, fibromuscular dysplasia, and endofibrosis

Abstract: In the general population, vascular causes of exercise-induced limb discomfort are most often the result of peripheral artery disease (PAD) due to atherosclerosis. However, several other clinical entities can often mimic the symptoms of atherosclerotic PAD of the lower extremities, particularly among younger patients with fewer risk factors for atherosclerosis, who often are more athletically fit than patients with PAD. Treatment for these entities often requires percutaneous or surgical intervention. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This can be confirmed with continuous wave Doppler signaling and pulse volume recordings with segmental pressures at rest and plantar flexion. Second, arterial duplex ultrasonography may demonstrate abnormalities when performed with the knee extended and the ankle in the neutral, dorsiflexed, and plantarflexed positions [12]. Caution should be maintained as a study of 16 healthy volunteers showed compression in 27 of 32 popliteal arteries when both lower extremities were measured during active plantar flexion [13].…”
Section: Popliteal Artery Entrapment Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…This can be confirmed with continuous wave Doppler signaling and pulse volume recordings with segmental pressures at rest and plantar flexion. Second, arterial duplex ultrasonography may demonstrate abnormalities when performed with the knee extended and the ankle in the neutral, dorsiflexed, and plantarflexed positions [12]. Caution should be maintained as a study of 16 healthy volunteers showed compression in 27 of 32 popliteal arteries when both lower extremities were measured during active plantar flexion [13].…”
Section: Popliteal Artery Entrapment Syndromementioning
confidence: 99%
“…Pathological specimens reveal fibrous thickening of the arterial wall, and any of the artery layers may be affected [36]. The variation in the arterial wall predisposes the vessel to aneurismal dilation, dissection, and distal embolization [12]. FMD can affect nearly any arterial bed, yet most commonly affects the renal arteries (75 % of the cases) with the carotid arteries being the second most affected.…”
Section: Fibromuscular Dysplasiamentioning
confidence: 99%
“…Because of its excellent spatial resolution, intra-arterial digital subtraction angiography (DSA) remains the best test to show endofibrosis lesions (3,4,13,17,18). However, qualitative and quantitative data on the angiographic appearance of arterial endofibrosis are not extensive because publications on the topic are limited to case reports or small series (1,2,10,13,14,19).…”
Section: Surgical Protocolmentioning
confidence: 99%
“…Arterial duplex ultrasonography may demonstrate abnormalities when performed in these provocative positions. 22 In a series of 16 healthy volunteers, popliteal artery compression was demonstrated in 84% of limbs on active plantar flexion, 23 highlighting the potential for falsepositive results. For this reason, dynamic computerized tomographic arteriography or magnetic resonance arteriography may be helpful to confirm the diagnosis.…”
Section: Popliteal Artery Entrapment Syndromementioning
confidence: 99%
“…Lower-extremity involvement may result in IC, microemboli, or (rarely) critical limb ischemia via dissection or rupture of the artery. 22,44 FMD is divided into several types according to which arterial layer is affected and by the arteriographic pattern of disease: medial fibroplasia, intimal fibroplasia, and adventitial (periarterial) hyperplasia. Medial fibroplasia is the most common type, making up 80% to 90% of cases in the renal arteries.…”
Section: Fibromuscular Dysplasiamentioning
confidence: 99%